Assessment of frictional-bond strength at the interface of single SSF in cementitious composite and prediction of accompanying pressure of surrounding matrix - Khabaz, Amjad (TAYLOR & FRANCIS LTD)
This paper deals with the study of bond in fiber-reinforced concrete composites and the effect of fiber/concrete interfacial friction on the fiber bond capacity. The paper presents the results of an experimental campaign including direct pull-out test of straight steel fiber-SSF embedded in concrete matrix, aimed at investigating the effect of some parameters, such as bonded length, yielding strength of steel fiber, fiber/concrete roughness, surrounding pressure of concrete matrix, and Poisson's ratio of concrete. Two analytical models based on the experimental results were proposed. Groups of single fiber embedded in concrete were prepared using different values of bonded length. The results showed that the frictional-bond strength, during fiber-slip stage, can be considered as constant despite changing the fiber embedment length. Furthermore, the SSF/concrete system can be considered as an elastic system, whereas the stress-displacement relation is semilinear. Finally, the results showed good improvements in the efficiency of frictional-bond strength when using fresh concrete with higher self-compacting, greater roughness at the interface of SSF/hardened-concrete, and fiber with lower yield strength. While no significant effect of Poisson's ratio on the frictional-bond strength was noticed.
Keywords: Straight steel fiber-SSF; friction; fiber-slip; frictional-bond strength; interface; Poisson's ratio